2016
DOI: 10.2337/db15-1141
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Receptor Activation Attenuates Platelet Aggregation and Thrombosis

Abstract: Short-term studies in subjects with diabetes receiving glucagon-like peptide 1 (GLP-1)-targeted therapies have suggested a reduced number of cardiovascular events. The mechanisms underlying this unexpectedly rapid effect are not known. We cloned full-length GLP-1 receptor (GLP-1R) mRNA from a human megakaryocyte cell line (MEG-01), and found expression levels of GLP-1Rs in MEG-01 cells to be higher than those in the human lung but lower than in the human pancreas. Incubation with GLP-1 and the GLP-1R agonist e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 50 publications
2
71
0
2
Order By: Relevance
“…The effect of GLP-1 analogs on hemostasis has been studied in vitro and in animal models. Human megakaryocytes have been found to express GLP-1 receptors and both human and murine blood incubated with the GLP-1 analog exenatide have been found to have reduced in vitro thrombus formation (44). Arterial thrombus formation decreased in mice treated with i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of GLP-1 analogs on hemostasis has been studied in vitro and in animal models. Human megakaryocytes have been found to express GLP-1 receptors and both human and murine blood incubated with the GLP-1 analog exenatide have been found to have reduced in vitro thrombus formation (44). Arterial thrombus formation decreased in mice treated with i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thrombus formation decreased in mice treated with i.v. exenatide, suggesting GLP-1 analogs to reduce platelet aggregation by inhibiting the release of α- and dense granules (44). Moreover, liraglutide has been shown to attenuate high-glucose-mediated PAI-1 expression in human endothelial cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Cameron‐Vendrig et al ( demonstrated an inhibitory action of the GLP‐1 receptor agonist exenatide on platelet aggregation ex vivo and thrombus formation in animals. In accord with our data, they were able to detect the presence of the GLP‐1 receptor on platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Gupta et al ( demonstrated anti‐aggregatory effects of the DPP‐4 inhibitor sitagliptin on human platelets without providing the mechanism underlying this phenomenon. In a recent publication, Cameron‐Vendrig et al () provided evidence for platelet inhibition by the GLP‐1 receptor agonist exenatide leading to reduced thrombus formation in an animal model. The authors also showed that the anti‐aggregatory and anti‐thrombotic effects of exenatide were associated with increased levels of cAMP.…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence, from publicly available transcriptome analyses such as the ImmGen (Immunological Genome) Project or from experimental studies in mice, localizes functional immune cell GLP-1R expression to a subset of intestinal intraepithelial lymphocytes (53). Similar challenges relate to interpretation of reports linking GLP-1R signaling to inhibition of platelet aggregation and reduced thrombosis in mice (54); notably, it is not yet clear from extensive transcriptomic analyses whether the canonical GLP-1R is expressed, detectable, and functional in mature platelets. Hence, more studies are needed of cells and tissues from animals and humans, ideally with experimental and clinical atherosclerosis and vascular dysfunction, to examine whether and how GLP-1 directly regulates immune cells or platelet biology through expression of the canonical GLP-1R.…”
Section: Inflammation and Hematopoietic Cellsmentioning
confidence: 97%